The Development of Citizen Networks Under the Democratic Monarchy for Volunteer Groups in Thepalai Sub-District, Kong District, Nakhon Ratchasima Province - Chokworakul, Settawat (King Prajadhipok’s Institute Journal, 2024)
The objectives of this research were 1) to study the problems and obstacles in the development of citizenship networks, 2) to study the methods of solving problems and obstacles in the development of citizenship networks, and 3) to study the approaches for developing citizenship networks under the democratic monarchy, with the King as head of the state. The study area focused on Thepalai Sub-District, Kong District, Nakhon Ratchasima Province. The sample group was 40 village health volunteers using participatory action research. The research results revealed that 1) the causes of problems and obstacles were the community leader’s lack of knowledge and understanding of fundamental laws, lack of publicizing on the role of citizenship under the constitution, and lack of promotion of public participation in citizenship. Regarding an online society, there is no report to the police on distorted and false information to the King’s Institute due to fear of being a threat to their families. 2) To solve problems and obstacles, the government agencies and educational institutions in the area must continuously promote citizenship networking to the people in the community, expand the knowledge of active citizenship to people who are not participating in the project, and provide online communication’s channel together with people in the community. These will increase the number of members in the networks and also provide a participatory meeting forum using the A-I-C process. 3) guidelines for a developing citizenship network under the democratic monarchy are followings: community’s leaders and people in the community must be self-reliant and implement the philosophy of King Rama IX’s sufficiency economy into their life, respecting the laws, rules and regulations of the community, agreeing to resolve conflicts in the community with the principles of compromise, learning to accept on majority’s consensus of the community, praising those who do good for community, including those who show respect for the law and honour the King’s institute, organizing an exhibition that shows the history and behaviour of a role model who obeys the law, respectfully act to the King’s institute, promoting a public volunteer’s system monitor that observe the government agencies’ works in the area, and also live broadcasting local council’s meetings through various channels in the community, encouraging representative’s public sectors to gain more knowledge and understanding of the regulations on procurement and rules of preparation planning. These will correctly check through the work of the local authorities.